KOMUNIKASI INTERNAL BADAN KEMAKMURAN MASJID (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Communication is a process when a person or several people, groups, organizations, and society create and use information to connect with the environment and other people. The Mosque Prosperity Board needs good communication, one of which is external communication. External communication is communication made by the organization/company through a management agreement to carry out communication activities with outside parties or the public outside the organization which is of course a concern. In prospering the mosque, a communication strategy is needed to revive the activity program at the mosque, then also to influence congregation to be interested in coming to the mosque. Thus, the mosque became prosperous. The mosque’s welfare agency can conduct external communication through magazines, media releases, speeches, brochures, posters, press conferences, social services and exhibitions.